Matthew Fontaine Maury: Pathfinder - Smith, Jason W (International Journal of Maritime History, 2016)
Historians have long recognized Matthew Fontaine Maury as an important if controversial figure in the histories of science and of maritime and naval affairs. These assessments, however, rest on scholarship that is by now more than a half-century old. It is therefore appropriate to look at Maury’s significance from fresh perspectives, incorporating recent historiographical trends in the history of science and cartography, environmental history, cultural history and military history. This article focuses on the ways in which Maury’s cartographic work reframed mariners’ understanding of the marine environment away from what he perceived to be a watery wilderness towards an ordered environment safe and favourable to American commerce. Maury was long known as ‘The Pathfinder of the Seas’, but I argue that his significance, in fact, lies in the ways he and his staff at the Naval Observatory organized the sea as a ‘common highway’, tracing paths, but also imposing narratives and constructing new meanings. Maury’s tool was the nautical chart and, particularly, his Wind and Current Charts series that by the 1850s reimagined the ways mariners, navigators and naval officers understood and harnessed the ocean environment. The article briefly considers these charts from three perspectives – method, process and representation – in order to see the ways in which Maury was pushing the boundaries of the cartographic medium to usher in revolutionary ways of envisioning the ocean environment. By quantifying winds, symbolizing whales and infusing the sea with ship tracks, among other things, Maury was imposing potent, if sometimes flawed, new ways of understanding and imagining the sea that were central to American maritime expansion in the antebellum era. In this and other ways, we can see Maury anew, a figure central to the growth of American commercial empire and to new ways of understanding and thinking about the sea.
Keywords: dept.his

Umayyad Caliphate - Judd, Steven C. (The Encyclopedia of Empire, 2016)
The Umayyad Caliphate (661–750) was the first Islamic dynasty. Muʿawiya ibn Abi Sufyan established himself as caliph in Damascus after his victory over ʿAli ibn Abi Talib in the civil war that followed the murder of ʿUthman ibn ʿAffan in Medina. Muʿawiya and his successors expanded the territory under Muslim rule dramatically. At their peak, the Umayyads ruled an empire stretching from Spain to the frontiers of China and India. The Umayyads made significant contributions to the development of the Islamic faith and to the spread of the Arabic language throughout the region. Dynastic crises, revenue shortfalls, and the limitations of an empire based on conquest ultimately led to their demise at the hands of the Abbasids in 750.
Keywords: 6th–10th centuries; Islam; Late Antiquity; Western Asia; dept.his; history; northern Africa; religious history

A Fantasy in Fashion: African American Empowerment in an Era of Opulence - Carter-David, Siobhan; Wu, Ellen (Race and Retail: Consumption across the Color Line, 2015)
Race has long shaped shopping experiences for many Americans. Retail exchanges and establishments have made headlines as flashpoints for conflict not only between blacks and whites, but also between whites, Mexicans, Asian Americans, and a wide variety of other ethnic groups, who have at times found themselves unwelcome at white-owned businesses.  Race and Retail documents the extent to which retail establishments, both past and present, have often catered to specific ethnic and racial groups. Using an interdisciplinary approach, the original essays collected here explore selling and buying practices of nonwhite populations around the world and the barriers that shape these habits, such as racial discrimination, food deserts, and gentrification. The contributors highlight more contemporary issues by raising questions about how race informs business owners’ ideas about consumer demand, resulting in substandard quality and higher prices for minorities than in predominantly white neighborhoods.  In a wide-ranging exploration of the subject, they also address revitalization and gentrification in South Korean and Latino neighborhoods in California, Arab and Turkish coffeehouses and hookah lounges in South Paterson, New Jersey, and tourist capoeira consumption in Brazil.   Race and Retail illuminates the complex play of forces at work in racialized retail markets and the everyday impact of those forces on minority consumers. The essays demonstrate how past practice remains in force in subtle and not-so-subtle ways.
Keywords: dept.his

Jean Marie Despiau: Unjustly Maligned Physician in the Medical Service of the Nguyen - Thompson, C. Michele (Vietnam and the West, 2010)
Keywords: dept.his

Swarms, Herds, and Peoples: Examinations of Interspecies Dynamics in China - Bello, David A.; Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2018)
Gale OneFile includes Swarms, Herds, and Peoples: Examinations of Interspecie by David A. Bello and C. Michele Thompson. Click to explore.
Keywords: dept.his

'Abd al-Rahman b. 'Amr al-Awza'i - Judd, Steven C. (Simon and Schuster, 2019)
‘Abd al-Rahman b. ‘Amr al-Awza‘i (c.707–774) was Umayyad Syria’s most influential jurist, part of a generation of scholars who began establishing the first formal structures for the preservation and dissemination of religious knowledge. Following the Abbasid revolution, they provided a point of stability in otherwise unstable times. Despite his close ties to the old regime, al-Awza‘i continued to participate in legal and theological matters in the Abbasid era. Although his immediate impact would prove short-lived, his influence on aspects of Islamic law, particularly the laws of war, endures to this day.
Keywords: Biography & Autobiography / Historical; History / General; History / Middle East / General; Law / Islamic; Religion / History; Religion / Islam / General; Religion / Islam / Theology; Social Science / Islamic Studies; dept.his

Sabbatical leave report: Fall 2013 - Nakamura, Byron (Distribution: Fall 2013 ; History., 2013)
This leave was devoted to research and revision of two conference papers submitted for publication, and to revision of a book chapter on boxing in the antiquity The chapter was submitted and accepted for publication in the Cambridge Companion to Boxing series.
Keywords: dept.his; faculty_collection; sabbatical_report

The Lion and the Lily: Map and Atlas Production in Early Modern England and France. - Petto, Christine Marie (2011)
Dr. Petto completed chapters 2 and 3 and a book proposal for her second manuscript, The lion and the lily: map and atlas production in early modern England and France. Chapter 2 describes local mapping and hydrographic charting initiatives in the 17th and 18th century; chapter 3 focuses on scientific cartography and the efforts of both crowns to map colonial interests in the Americas and Asia. She obtained book contract with Lexington Books, with release date of July 2013.
Keywords: dept.his; faculty_collection; sabbatical_report

Friday Night Fighter: "Indio" Ortega and the Golden Age of Televised Boxing. - Rondinone, Troy (Spring ; History., 2011)
Keywords: dept.his; faculty_collection; sabbatical_report

A History of Smallpox and Preventive Treatments for It in the Lands Bordering the South China Sea - Thompson, C. Michele (2011)
Keywords: dept.his; faculty_collection; sabbatical_report

The Saints of Progress: A History of Coffee, Migration, and Costa Rican National Identity - Kordick, Carmen (The University of Alabama Press, 2019)
"This work narrates the development of a historically remote--although internationally celebrated--coffee-growing region from the early 19th century through to the first decade of the 21st century. It considers the nation-building process from the margins to question traditional scholarly works that have reproduced, rather than deconstructed, Costa Rica's exceptionalist national mythologies that imagine this isthmian republic as Central America's 'white,' democratic, nonviolent, and egalitarian republic. The book recognizes that even though Costa Rica's exceptionalist rendition draws on some undeniable realities, it thoughtfully considers the origins, applicability, and longevity of the different elements of this exceptionalist master narrative. In particular, it suggests the mythology emerged during the Cold War, as revolution, civil war, military dictatorship, and state violence plagued much of Central America. In this same period, Costa Rica not only retained a relatively stable democratic system, but policymakers eliminated the standing army in 1948. This widely embraced and celebrated historical narrative, however, distorts as much as it illuminates the experience of contemporary and historical actors"--
Keywords: Coffee industry; Costa Rica; Costa Rica; History; Political aspects; dept.his

Sabbatical report on Contesting the Origins of the First World War - Paddock, Troy R. E. (2019)
Dr. Paddock spent the year completing a book and revising an article.
Keywords: dept.his; faculty_collection; sabbatical_report

Nightmare Factories The Asylum in the American Imagination - Rondinone, Troy (Johns Hopkins University Press, 2019)
Keywords: History; History; Asylums; Psychiatric hospitals; United States; dept.his; faculty_collection

To Master the Boundless Sea: The U.s. Navy, the Marine Environment, and the Cartography of Empire - Smith, Jason W. (Flows, migrations, and exchanges, 2018)
"As the United States grew into an empire in the late nineteenth century, notions like 'sea power' derived not only from fleets, bases, and decisive battles, but also from a scientific effort to understand and master the ocean environment. Beginning in the early nineteenth century and concluding in the first years of the twentieth, Jason W. Smith tells the story of the rise of the U.S. Navy and the emergence of American ocean empire through its struggle to control nature. In vividly told sketches of exploration, naval officers, war, and, most significantly, the ocean environment, Smith draws together insights from environmental, maritime, military, and naval history, and the history of science and cartography, placing the U.S. Navy's scientific efforts within a broader cultural context"--
Keywords: History, Naval; History; Cartography; Imperialism and science; United States; History; Nautical charts; SCSU Faculty Scholar Award; United States; United States. Navy; award_winner; dept.his; faculty_collection

Human Rights in the People's Republic of China - Wu, Yuan-li; Chang, Maria Hsia; Cooper, John F.; Gregor, A. James; Michael, Franz H.; Lee, Ta-ling (Westview special studies on China and East Asia, 2018)
Keywords: 20th century; Human rights; 21st century; China; History; Human rights; dept.his; faculty_collection

New Perspectives on Ibn ʻAsākir in Islamic Historiography - Judd, Steven C.; Scheiner, Jens J. (Islamic history and civilization ; v. 145, 2017)
This volume contains six articles on Ibn 'Asākir and his 'Ta'rīkh madīnat Dimāshq' illustrating a variety of perspectives and approaches to the material. It includes a seventh article that discusses the process by which the now standard 'Dār al-fikr' edition was compiled. The contributions address both the geographical and biographical sections of the 'Ta'rīkh madīnat Dimashq'. Some of the authors examine Ibn 'Asākir's sources, while others describe how Ibn 'Asākir's works were used by later generations of scholars and how he influenced multiple genres of later writings. The volume also contains analyses of individual biographies and discussions of Ibn 'Asākir's treatment of larger classes of people, including the first analysis of his biographies of women. In sum, it illustrates both the wide range of topics that the 'Ta'rīkh madīnat Dimashq' covers and the latest techniques for analyzing Ibn 'Asākir and his work.
Keywords: Historiography; Ibn ʻAsākir, ʻAlī ibn al-Ḥasan, 1105-1176. Tārīkh madīnat Dimashq; Islamic Empire; dept.his; faculty_collection

This City Belongs to You: A History of Student Activism in Guatemala, 1944-1996 - Vrana, Heather A. (University of California Press, 2017)
"Between 1944 and 1996, Guatemala experienced a revolution, counterrevolution, and civil war. In the middle of these national shifts were students from Guatemala's only public university, the University of San Carlos (USAC). USAC students served in, advised, protested, and were later persecuted by the government, all the while crafting a powerful student nationalism founded on their responsibility to lead the nation. In no other moment has the relationship between the university and the state been so mutable, yet so mutually formative. By showing how the very notion of the middle class in Guatemala emerged from these student movements, this book places an often-marginalized region and period at the center of histories of class, protest, and youth movements, while providing an entirely new way to think about the role of universities and student bodies in the formation of liberal democracy throughout Latin America.
Keywords: 20th century; Guatemala; History; Student movements; dept.his; faculty_collection

An Academy at the Court of the Tsars: Greek Scholars and Jesuit Education in Early Modern Russia - Chrissidis, Nikolaos A. (NIU Press, 2015)
Keywords: 17th century; 17th century; Education, Higher; 17th century; Greeks; Education; History; History; Jesuits; Leichoudēs, Iōannikios, 1633-1717; Leichoudēs, Sōphronios, 1652-1730; Moskovskai︠a︡ slavi︠a︡no-greko-latinskai︠a︡ akademii︠a︡; Moscow; Russia; Russia (Federation); dept.his; faculty_collection

Our Land, Our Life, Our Future: Black South African Challenges to Territorial Segregation, 1913-1948 - Feinberg, Harvey M. (Hidden histories series, 2015)
Keywords: 1909-1961; History; History; South Africa; Land reform; Law and legislation; South Africa; dept.his; faculty_collection

Major Problems in American Indian History: Documents and Essays - Hurtado, Albert L.; Iverson, Peter; Bauer, William J.; Amerman, Stephen Kent (Major problems in American history series, 2015)
Keywords: History; History; Indians of North America; Indians of North America; Sources; dept.his; faculty_collection

Mapping and Charting in Early Modern England and France: Power, Patronage, and Production - Petto, Christine Marie (Toposophia, 2015)
Keywords: Cartography; England; France; History; History; Cartography; History; Map industry and trade; Paris; dept.his; faculty_collection

Vietnamese Traditional Medicine: A Social History - Thompson, Claudia Michele (History of medicine in Southeast Asia series, 2015)
Keywords: History; Medicine, Chinese; History; Vietnam; Medicine, Traditional; SCSU Faculty Scholar Award; Vietnam; award_winner; dept.his; faculty_collection; history; Medicine, Chinese Traditional; history; Smallpox; prevention & control; Traditional medicine

World War I and Propaganda - Paddock, Troy R. E. (History of warfare ; v. 94, 2014)
Keywords: Propaganda; World War, 1914-1918; dept.his; faculty_collection

Dr. Ruth A. Parmelee and the Changing Roll of Near East Missionaries in Early Twentieth Century Turkey - Metaxas, Virginia (Role of the American Board in the World: Bicentennial Reflections on the Organization's Missionary Work, 1810-2010, 2012)
The American Board of Commissioners for Foreign Missions (ABCFM) was the country's first creator of overseas Christian missions. Founded in 1810 and supported by a coalition of Calvinist denominations, the ABCFM established the first American missions in India, China, Africa, Oceania, the Middle East, and many other places. It was America's largest missionary organization in the nineteenth century, and its influence was immense. Its missionaries established the first Western schools and hospitals in many parts of the world, and they successfully promoted women's rights and other ideals from the Enlightenment. They also transformed oral languages such as Zulu, Hawaiian, and Cherokee into written form, and they preserved many elements of premodern cultures (albeit not always intentionally). The contributors to this book provide valuable insights on the work of the ABCFM (which exists today under a different name). Some of the contributors profile the lives of notable ABCFM missionaries, others focus on ideological shifts within the Board, and still others chronicle the Board's role in historic events, including the Opium Wars, the colonization of Hawai'i, and the Armenian Genocide. From reading this book, people will come to understand why the ABCFM is widely viewed as America's most historically significant missionary organization.
Keywords: American Board of Commissioners for Foreign Missions; History; Congregational churches; Missions; Missions, American; dept.his; faculty_collection

Southern Medicine for Southern People Vietnamese Medicine in the Making - Monnais-Rousselot, Laurence; Thompson, Claudia Michele; Wahlberg, Ayo (Cambridge Scholars Pub., Cambridge Scholars Publishing, 2012)
What is a national medicine? What does it mean for a medicine to be traditional and scientific at the same time? How could a specifically Vietnamese medicine emerge out of the medical practices and treatments that have flourished and waned during key soci
Keywords: History; Traditional medicine; Vietnam; Vietnam; Traditional medicine; dept.his; faculty_collection

Religion and Identity in Russia and the Soviet Union A Festschrift for Paul Bushkovitch - Chrissidis, Nikolaos A. (Slavica Publishers, Slavica, 2011)
Keywords: Bushkovitch, Paul; Nationalism; History; Christianity and politics; History; Identity (Psychology); History; Nationalism; History; Soviet Union; Politics and government; Politics and government; Russia; Religious aspects; Russia; Russkai͡a pravoslavnai͡a t͡serkovʹ; National characteristics, Russian; Soviet Union; dept.his; faculty_collection

We Will Be Satisfied with Nothing Less: The African American Struggle for Equal Rights in the North During Reconstruction - Davis, Hugh (Cornell University Press, 2011)
Historians have focused almost entirely on the attempt by southern African Americans to attain equal rights during Reconstruction. However, the northern states also witnessed a significant period of struggle during these years. Northern blacks vigorously protested laws establishing inequality in education, public accommodations, and political life and challenged the Republican Party to live up to its stated ideals. In "We Will Be Satisfied With Nothing Less," Hugh Davis concentrates on the two issues that African Americans in the North considered most essential: black male suffrage rights and equal access to the public schools. Davis connects the local and the national; he joins the specifics of campaigns in places such as Cincinnati, Detroit, and San Francisco with the work of the National Equal Rights League and its successor, the National Executive Committee of Colored Persons. The narrative moves forward from their launching of the equal rights movement in 1864 to the "end" of Reconstruction in the North two decades later. The struggle to gain male suffrage rights was the centerpiece of the movement's agenda in the 1860s, while the school issue remained a major objective throughout the period. Following the ratification of the Fifteenth Amendment in 1870, northern blacks devoted considerable attention to assessing their place within the Republican Party and determining how they could most effectively employ the franchise to protect the rights of all citizens.-- Book jacket.
Keywords: 1863-1877; African Americans; 19th century; Equality before the law; 19th century; Reconstruction (U.S. history, 1865-1877); African Americans; Civil rights; History; United States; dept.his; faculty_collection

Urban Indians in Phoenix schools, 1940-2000 - Amerman, Stephen Kent (Indigenous education, 2010)
"In the latter half of the twentieth century, tens of thousands of Native American families moved to cities across the United States, some via the government relocation program and some on their own. In the cities, they encountered new forms of work, entertainment, housing, and education. In this study, Stephen Kent Amerman focuses on the educational experiences of Native students in urban schools in Phoenix, Arizona, a city with one of the largest urban Indian communities in the nation. The educational experiences of Native students in Phoenix varied over time and even in different parts of the city, but interactions with other ethnic groups and the experience of being a minority for the first time presented distinctive challenges and opportunities for Native students., Using oral histories as well as written records, Amerman examines how the Phoenix schools tried to educate and assimilate the Native students alongside Hispanic, Asian, black, and white students and how Native children, their parents, and the Indian community at large responded to this new urban education and the question of their cultural identity. Reconciling these pressures was a struggle, but many found resourceful responses, charting paths that enabled them to acquire an urban education while still remaining Indian."--Pub. desc.
Keywords: 20th century; 20th century; Education; 20th century; Indians of North America; 20th century; Public schools; 20th century; Urban schools; 20th century; Urbanization; Arizona; Cultural assimilation; Education; History; Indians of North America; Phoenix; Social aspects; award_winner; dept.his; faculty_collection

The Great Industrial War Framing Class Conflict in the Media, 1865-1950 - Rondinone, Troy (Rutgers University Press, 2010)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers. Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported.
Keywords: History; History; Social conflict; Labor disputes; United States; dept.his; faculty_collection

Sex, drink, and drugs: Tobacco in seventeenth-century Russia - Chrissidis, N.A. (Tobacco in Russian History and Culture: From the Seventeenth Century to the Present, 2011)
Keywords: dept.his

Manufacturing Mohism in the Mencius - Radice, T. (Asian Philosophy, 2011)
The Mencius contains several negative remarks about the Mohists and their doctrine of 'universal love' (jian'ai). However, little attention has been paid to whether Mencius' descriptions of Mohism were accurate. Fortunately, there is a surviving record of the beliefs of Mozi in the text that bears his name. In this essay, I analyze this text and descriptions of Mohism from other early Chinese texts, and compare them to the criticisms of Mohism in the Mencius. Ultimately, I show that the image of the Mohists as ones who promoted a doctrine that contradicted filial piety was inaccurate, and obscured the complexities of filial piety in the Warring States period. © 2011 Taylor and Francis.
Keywords: dept.his; peer-reviewed

Ella Grasso: Connecticut's pioneering governor - Purmont, J.E. (Ella Grasso: Connecticut's Pioneering Governor, 2012)
When Ella Tambussi Grasso ran for governor of Connecticut in 1974, she had not lost an election since she was first voted into the state's General Assembly in 1952. The people of Connecticut chose her as the nation's first woman to be elected governor in her own right-the capstone of a long and successful career dedicated to public service, effective government, and the democratic process. During her tenure as governor, Grasso's leadership was tested in the face of fiscal problems, state layoffs, and budget shortfalls. The daughter of Italian immigrants, she endeared herself to her constituents during the great Blizzard of 1978, when she stayed at the State Armory around the clock to direct emergency operations and make frequent television appearances. Author Jon E. Purmont, who served as Grasso's executive assistant when she was governor, draws on his diary from that time, research in Grasso's archives, and interviews with Grasso's family and friends to give us a rich and intimate portrait of this political pioneer. © 2012 Jon E. Purmont. All rights reserved.
Keywords: dept.his

Would a saola by any other name still be a saola?: Appropriating rare animals, expropriating minority peoples - Thompson, C.M. (State, Society and the Market in Contemporary Vietnam: Property, Power and Values, 2012)
Keywords: dept.his

Divergent paths: Processes of identity formation among German speakers, 1730-1760 - McDaniel, M.B. (A Peculiar Mixture: German-Language Cultures and Identities in Eighteenth-Century North America, 2013)
Keywords: dept.his

Friday Night Fighter: Gaspar "Indio" Ortega and the Golden Age of Television Boxing - Rondinone, Troy (University of Illinois Press, 2013)
Friday Night Fighter relives a lost moment in American postwar history, when boxing ruled as one of the nation's most widely televised sports. During the 1950s and 1960s, viewers tuned in weekly, sometimes even daily, to watch widely-recognized fighters engage in primordial battle, with the Gillette Cavalcade of Sports Friday Night Fights being the most popular fight show. Troy Rondinone follows the dual narratives of the Friday Night Fights show and the individual story of Gaspar "Indio" Ortega, a boxer who appeared on primetime network television more than almost any other boxer in history. From humble beginnings growing up poor in Tijuana, Mexico, Ortega personified the phenomenon of postwar boxing at its greatest, appearing before audiences of millions to battle the biggest names of the time, such as Carmen Basilio, Tony DeMarco, Chico Vejar, Benny "Kid" Paret, Emile Griffith, Kid Gavilan, Florentino Fernández, and Luis Manuel Rodriguez.--(Source of description unspecified.)
Keywords: Hispanic Americans; History; History; Boxing; History; Television broadcasting of sports; Ortega, Gaspar "Indio", 1935-; Boxing; United States; United States; Sports; dept.his; faculty_collection

Greeks in seventeenth-century Russia - Chrissidis, N.A. (Portraits of Old Russia: Imagined Lives of Ordinary People, 1300-1745, 2015)
Keywords: dept.his

Soul sister journey: Essence magazine and travel columns during the “me” decad - Carter-David, S. (Women's Magazines in Print and New Media, 2016)
Keywords: dept.his

Were the umayyad-era qadarites Kāfirs? - Judd, S. (Islam. Hist. Civiliz., 2016)
Keywords: dept.his

Platonic words: Paolo sarpi and roberto bellarmino as translators in the venetian interdict crisis - Kern, D. (Philological Quarterly, 2016)
Keywords: dept.his; ⛔ No DOI found

To know the distance: Wayfinding and roadmaps of early modern England and France - Petto, C.M. (Cartographica, 2016)
In 1675, John Ogilby produced his road atlas with strip maps which not only arrived with fanfare, but spawned several more publications that aimed to be user-friendly. As with many maps and atlases from the London printing trade, the objectives were to serve consumers, acquire a piece of the market, and have an outlet for a new edition. Across the Channel, however, the road network of France, as with other public works, was not only state-directed but a tool of state power. Not until nearly one hundred years later did Claude-Sidoine Michel and Louis-Charles Desnos produce L'Indicateur Fidele, which provided strip maps for merchants, navigators, and travelers. This publication emerged out of the French national mapping project directed by the Cassini family. In the interim, while French map makers produced maps with an appeal to serving the state, they, like their London contemporaries, also hoped to maintain a thriving business and attract an audience, often through the traditional French social institution of patronage. The purpose of this comparative study of (post) road maps and atlases of England and France is to investigate the role of the government and the publishing trade in the production of these works. © 2016 University of Toronto Press.
Keywords: Consumers; England; France; London [England]; Map trade; Patronage; Post roads; Strip maps; United Kingdom; cartography; dept.his; mapping

Thou uncracked keel: The many voyages of the Whaleship Charles W. Morgan and the presence of the American Maritime past - Smith, J.W. (New England Quarterly-A Historical Review of New England Life and Letters, 2016)
The ship wherein Theseus and the youth of Athens returned from Crete had thirty oars, and was preserved by the Athenians down even to the time of Demetrius Phalereus, for they took away the old planks as they decayed, putting in new and stronger timber in their place, in so much that this ship became a standing example among the philosophers, for the logical question of things that grow; one side holding that the ship remained the same, and the other contending that it was not the same. © 2016 by The New England Quarterly. All rights reserved.
Keywords: dept.his

The lands of orthodoxy in the seventeenth century circa 1590-1720 - Bushkovitch, P.; Chrissidis, N.A.; Pǎun, R.G. (Cahiers du Monde Russe, 2017)
Keywords: dept.his

Signum meum apposui: Notaries and their signs in medieval languedoc - Friedlander, A. (The Experience of Power in Medieval Europe, 950-1350, 2017)
Keywords: dept.his

To the editors - Forbes, R.P.; Mintz, S.; Stauffer, J. (American Historical Review, 2019)
Keywords: dept.his; ⛔ No DOI found

Intellectuals and “democratic elements”: A distrusted underclass - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
As the targets of numerous campaigns, intellectuals have sustained mental torment and physical suffering on a large scale. Like the deprivation of human rights for biological and genetic reasons in other lands or other ages, Chinese intellectuals were destined to suffer abridgement of their human rights in the People’s Republic of China for political and ideological reasons. The term “intellectuals” refers to all those who have had a middle school/higher education and those with similar educational levels. Included in the ranks of intellectuals were members of the so-called democratic parties. These people, never large in number, were mostly well educated and well known in intellectual circles. The Cultural Revolution will be long remembered by intellectuals not only as a period of continued mental torment from the earlier days, but more particularly as a period of the most cruel physical abuses in human history. Intellectuals, deprived of their most precious human rights, continue to exist in mainland China as an underclass. © 1988 by Taylor & Francis. All rights reserved.
Keywords: dept.his

Red guards and political dissidents (I): Tools of violence and power struggle - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
In 1966, Mao Zedong launched the Great Proletarian Cultural Revolution in a last attempt to remake China in his image. He believed that the country was led by a party infested from the top on down with “capitalist-roaders” who had betrayed the proletarian goals of true socialism by following the bourgeois line. Denied support in the power structure, Mao sought help from the outside, mobilizing millions of high school and college students as the “Red Guards” to strike down his enemy in an unprecedented campaign that left the nation nearly paralyzed. Red Guard organizations of confusing ideological persuasions soon proliferated throughout the country, and the whole movement quickly got out of control and degenerated into total chaos. That the Red Guards were used by Mao as a tool in the ideologically based power struggle within the party is not only the consensus of most observers but also has been freely admitted by many former Red Guards. © 1988 by Taylor & Francis. All rights reserved.
Keywords: dept.his

Red guards and political dissidents (II): Victims beyond a generation - Lee, T.-L. (Hum. Rights in the People's Repub. of China, 2019)
Many former Red Guards who through the Cultural Revolution were encouraged to participate in unrestrained violence, saw the seamy side of the regime as a result and were themselves eventually suppressed and reached the conclusion that the system was corrupt and had to be changed. Former Red Guards who turned political activists varied greatly in their often vaguely defined outlooks and their intensity of commitment and activity. Wei Jingsheng, China’s most celebrated Red Guard-turned dissident, related a similar experience in an unfinished autobiographical account written before his arrest and smuggled out of the country in 1980. Many former Red Guards understandably see a silver lining in the destructive rampage they committed during the height of the Cultural Revolution. The Red Guard movement has come full circle. The human rights tragedy of the movement is threefold. In the first stage, the Red Guards were Mao’s “little generals” trampling on the human rights of their victims. © 1988 by Taylor & Francis. All rights reserved.
Keywords: dept.his

Prime (and crime) time: Boxing in the 1950s - Rondinone, T. (The Camb. Companion to Box., 2019)
Keywords: dept.his

Human rights in the people’s republic of China - Wu, Y.-L.; Michael, F.; Copper, J.F.; Lee, T.-L.; Chang, M.H.; Gregor, A.J. (Human Rights in the People's Republic of China, 2019)
This book examines the effects that political institutions, the legal system, and economic policies have had on the human rights record in the PRC since 1949. The authors first address the problems of assessing political liberties in a nation that emphasizes economic over civil rights and that has traditionally valued collective rights over individ. © 1988 by Taylor & Francis. All rights reserved.
Keywords: dept.his

Bridges: Technology and the Social - Paddock, Troy R. E. (Environment, Space, Place, 2010)
Keywords: dept.his

“No Man’s Land”: Forbidden and Subversive Space in War - Paddock, Troy R. E. (Environment, Space, Place, 2013)
Keywords: dept.his

Spatial relations and the struggle for space: Friedrich Ratzel’s impact on German education from the Wilhelmine Empire to the Third Reich - Paddock, Troy (Journal of Educational Media, Memory, and Society, 2016)
This article examines the influence of Friedrich Ratzel’s idea of the struggle for space and its impact on cultural and national development depicted in German geography and history textbooks from the Wilhelmine era to the Third Reich. Ratzel’s concept of bio-geography conceived the state as a living organism that is the product of humanity’s interaction with the land and also facilitates humanity’s spread across the earth. German textbooks promoted a similar concept of the state in their portrayal of geography and history, the implications of which were appropriated by the National Socialists to support their geopolitical goals.
Keywords: Education; Friedrich ratzel; Geography instruction; History instruction; National identity; State; Textbooks; dept.his

Creating the Russian Peril: Education, the Public Sphere, and National Identity in Imperial Germany, 1890-1914 - Paddock, Troy R. E. (Camden House, 2010)
German attitudes toward and stereotypes of Russia before the First World War and how they were inculcated in the public.
Keywords: 1871-1918; 19th century; Education; 19th century; Nationalism; 20th century; Germany; 20th century; Nationalism; Foreign public opinion, German; Russia; Germany; Germany; Germany; Germany; Russia; History; History; Education; Political aspects; Press coverage; Public opinion; Relations; Russia; Russia; SCSU Faculty Scholar Award; award_winner; dept.his; faculty_collection

World War I and Propaganda - Paddock, Troy R. E. (History of warfare, 2014)
World War I and Propaganda offers a new look at a familiar subject. The contributions to this volume demonstrate that the traditional view of propaganda as top-down manipulation is no longer plausible. Drawing from a variety of sources, scholars examine the complex negotiations involved in propaganda within the British Empire, in occupied territories, in neutral nations, and how war should be conducted. Propaganda was tailored to meet local circumstances and integrated into a larger narrative in which the war was not always the most important issue. Issues centering on local politics, national identity, preservation of tradition, or hopes of a brighter future all played a role in different forms of propaganda. Contributors are Christopher Barthel, Donata Blobaum, Robert Blobaum, Mourad Djebabla, Christopher Fischer, Andrew T. Jarboe, Elli Lemonidou, David Monger, Javier Pounce,Catriona Pennell, Anne Samson, Richard Smith, Kenneth Andrew Steuer, María Inés Tato, and Lisa Todd.
Keywords: dept.his

Captured on the gold coast: “Illegal” enslavement, freedom and the pursuit of justice in dutch courts, 1746–1750 - de Kok, Gerhard; Feinberg, Harvey M. (Journal of Global Slavery, 2016)
In May of 1746, slaving captain Christiaan Hagerop illegally captured ten Gold Coast canoe paddlers, seven of whom were free Africans from Elmina and Fante. Hagerop subsequently sailed to Suriname, where he sold the paddlers into slavery. To appease the relatives of the captured men and to safeguard its reputation among local Africans, the Dutch West India Company (WIC) launched a search for the kidnapped paddlers. Six of the men were eventually located in Suriname in 1749, the seventh having died in slavery. While the Africans were transported back to the Gold Coast via Amsterdam, the WIC tried to have Hagerop extradited to its Gold Coast possessions to receive punishment for his crime. A legal battle over jurisdictional competence ensued in the Dutch Republic, the outcome of which was that the captain was made to stand trial in Amsterdam, but in the end he received very little punishment. © 2016 Copyright 2016 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: Africa; Gold Coast; Slave Trade; Suriname; dept.his; wic

The World of Eastern Orthodoxy - Chrissidis, Nikolaos A. (The Oxford Handbook of Early Modern European History, 1350-1750, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Keywords: dept.his

The early qadariyya - Judd, Steven C. (The Oxford Handbook of Islamic Theology, 2014)
This article discusses the briefly significant Qadariyya movement during the Umayyad period, with an emphasis on how the movement and its adherents were treated in later sources. The article examines the doctrine of human free will advocated by the Qadariyya, exploring the impetus behind their theological viewpoints and the doctrinal complications that accompanied human free will. It also addresses the debate about the origins of both the doctrine and the movement, and the significance of accusations of Christian roots. The article discusses the views ascribed to prominent Qadari leaders, including Maʿbad al-Juhanī and Ghaylān al-Dimashqī, as well as the systematic persecution of the Qadariyya, led by al-Awzāʿī. It also examines the politicization of the Qadariyya and their entanglement with Yazīd (III) b. al-Walīd’s rebellion during the third fitna. Finally, the article addresses the eclipse of the Qadariyya by the Muʿtazilites.
Keywords: dept.his

Religious Scholars and the Umayyads: Piety-Minded Supporters of the Marwānid Caliphate - Judd, Steven C. (Culture and civilisation in the Middle East, 2014)
Keywords: Doctrines; History; Judges (Islamic law); History; Muslim scholars; Islamic law; SCSU Faculty Scholar Award; Umayyad dynasty; Islam; award_winner; dept.his; faculty_collection

Muslim Persecution of Heretics during the Marwānid Period (64–132/684–750) - Judd, Steven (Al-Masaq: Journal of the Medieval Mediterranean, 2011)
This article traces the emergence of a systematic approach to combating heresy during the Umayyad period. It argues that the Umayyads sought to silence religious dissent by labelling it as heresy and that the doctrinal boundaries of orthodoxy narrowed as the Umayyad period progressed. The article also asserts that Umayyad efforts to impose their vision of orthodoxy were an important precedent for the mihna under the Abbasids. © 2011 Society for the Medieval Mediterranean.
Keywords: Abd al-Malik; Ghaylan al-Dimashqi; Heretic; Hisham; Islam - heresy; Islamic scholar; Mabad al-Juhani; Qadariyya; Theological movement; Ummayad caliph; Ummayad caliphate; dept.his

The persistence of republicanism: class war talk, american style - Cassano, Graham; Rondinone, Troy (Labor Studies Journal, 2010)
The authors argue that there have been moments in American history when a class analysis entered into popular discourse. What has been "exceptional" about American history is the manner in which that class analysis emerged. When Americans speak the language of "class" and "class warfare," it is often clothed in the rhetoric of labor republicanism. That is, rather than offering a systemic analysis of capitalist processes, American labor republicanism offers a class analysis that sets a small set of bad acting "elites" and their dependents against the mass of American workers. The authors trace this discourse from Franklin Roosevelt's 1936 description of "economic royalists" to Lou Dobbs's nativist attack on "corporate elites" and undocumented workers. As the United States enters a new period of "class awareness" and economic crisis, this republicanism returns to haunt public discourse. © 2010 UALE.
Keywords: Franklin D. Roosevelt; Lou Dobbs; Marxian analysis; class warfare; dept.his; labor republicanism

Sinification as Limitation: Minh Mạng’s Prohibition on Use of Nôm and the Resulting Marginalization of Nôm Medical Texts - Thompson, C. Michele (Looking at it from Asia: the Processes that Shaped the Sources of History of Science, 2010)
For Vietnamese scholars in the late eighteenth and early nineteenth centuries reading and writing ability in both Chinese and Nôm (an ideographic writing system used to write Vietnamese) was considered an essential tool of scholarship and literary expression.
Keywords: Chinese Character; Imperial Examination System; Medical Text; Royal Court; Vietnamese Language; dept.his

The Folklore of Deinstitutionalization: Popular Film and the Death of the Asylum, 1973–1979 - Rondinone, Troy (Journal of American Studies, 2019)
The demise of America's state mental hospital system, or “deinstitutionalization,” has received much attention from sociologists and historians of medicine. Less understood is the manner in which the public experienced and came to terms with it. Using elements of folklore and horror studies, I will examine how popular films accommodated audiences to institutional decline and confirmed popular antistatist pessimism. The Exorcist (1973), One Flew over the Cuckoo's Nest (1975), Halloween (1978), and When a Stranger Calls (1979) helped weave a tapestry of distrust. By endorsing popular conceptions of institutional failure and presenting mythical narratives of individualist triumph, these films helped pave a path towards the conservative Reagan era to come.
Keywords: dept.his; peer-reviewed

Lovecraft Meets the Mummy: Orientalism, Race, and Monstrous Egypt in “Imprisoned with the haraohs” and “Out of the Aeons” - Rondinone, Troy (Lovecraftian Proceedings No. 3., 2019)
Keywords: dept.his; faculty_collection

The unforgettable age: young in Costa Rica of XX century - Coury Kordick, Carmen Coury (Americas, 2019)
Keywords: dept.his; peer-reviewed

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge, 2019)
Contesting the Origins of the First World War challenges the Anglophone emphasis on Germany as bearing the primary responsibility in causing the conflict and instead builds upon new perspectives to reconsider the roles of the other Great Powers. Using the work of Terrance Zuber, Sean McMeekin, and Stefan Schmidt as building blocks, this book reassesses the origins of the First World War and offers an explanation as to why this reassessment did not come about earlier. Troy R.E. Paddock argues that historians need to redraw the historiographical map that has charted the origins of the war. His analysis creates a more balanced view of German actions by also noting the actions and inaction of other nations. Recent works about the roles of the five Great Powers involved in the events leading up to the war are considered, and Paddock concludes that Germany does not bear the primary responsibility. This book provides a unique historiographical analysis of key texts published on the origins of the First World War, and its narrative encourages students to engage with and challenge historical perspectives.
Keywords: dept.his

‘Mixt marriages’: Ethnic and religious intermarriage among German-speakers in eighteenth-century Pennsylvania - McDaniel, Marie Basile (The History of the Family, 2019)
Civil and religious authorities in eighteenth-century America grew increasingly concerned over the freedom with which young people chose their marriage partners. Correlating racial, religious and cultural similarity in marriage to a stable society, these authorities attempted to limit marriage and sexual choices by requiring parental authority for marriage, distributing permits to a select few to perform marriages, and criminalizing racial miscegenation. Eighteenth-century Pennsylvania German authorities supported this attitude because they associated ethnic and religious out-marriage with the weakening of the body and the destruction of society. My study uses the marriage and birth records of eighteenth-century Pennsylvania Germans to examine their marriage and sexual relationships. I discovered that Pennsylvania Germans overwhelmingly chose to marry other German-speakers, out of proportion with their population. By examining the then available works on marriage and procreation, I discovered that Pennsylvania Germans read works that emphasized the necessity and importance of intra-ethnic and religious sex and marriage for the health of their children. Pennsylvania Germans chose their marriage partners in alignment with their community’s attitudes towards those of other ethnicities and religions. A small data set further suggests that relationships with non-Germans occurred but rarely became formalized. This complicates what we know about the sexual and emotional revolutions in the seventeenth and eighteenth centuries; far from a linear progression of attitudes towards sex, marriage, and others, eighteenth-century Pennsylvania Germans expressed multiple, contextually-driven perspectives, and in the process they created and maintained strong ethnic communities. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Defoe; German (citizen); German-speakers; Marriage; Pennsylvania; article; child; colonial; dept.his; destruction; ethnicity; female; human; human experiment; male; marriage; peer-reviewed; pre-marital; religion

Roman exempla in the early Tudor period - Kern, Darcy (English: Journal of the English Association, 2019)
Abstract. Roman exempla, or moralizing anecdotes, appear frequently in the English literature of the early Tudor period. Textual, authorial, and historical exe
Keywords: dept.his; peer-reviewed

Empire by invitation: William Walker and manifest destiny in Central America - Coury Kordick, Carmen (Americas, 2019)
Keywords: book.review; dept.his; peer-reviewed

Boxing in the ancient world - Nakamura, Byron J. (The Cambridge Companion to Boxing, 2019)
Keywords: dept.his

Beyond borders: Jean Gerson’s conciliarism in fifteenth-century Spain - Kern, Darcy (Renaissance and Reformation, 2019)
In recent years there has been renewed interest in conciliarism, the belief that the authority of the universal church resides in an ecumenical council, not the pope, though the perception remains that conciliarism had a negligible impact in Iberia. One way to better understand the evolution of conciliar thought in the Spanish kingdoms is by looking at the circulation of the works and ideas of the French conciliarist Jean Gerson (1363–1429). Though a complete reconstruction of Gerson’s circulation is impossible, one can offer an initial overview of his impact in the Spanish kingdoms not simply by counting manuscripts or incunabula, as valuable as that is, but by thinking broadly about networks of exchange and dissemination. Gerson’s works came to Spain through the church councils, trans-Pyrenees Carthusian networks, monastic reformers, printers and printing houses, mendicant reformers, and the library of the University of Salamanca. © 2019, (publisher Name). All Rights Reserved.
Keywords: dept.his; peer-reviewed

Rolf Brandt and a conservative literary journalism - Paddock, Troy RE (Literary Journalism Studies, 2019)
Rolf Brandt (1886-1953) was a German journalist, author, and political commentator. His first work was as a war reporter on the Eastern Front during the opening months of the Great War (World War I). His reports appeared in several important German newspapers (Norddeutsche Allgemeine Zeitung and Frankfurter Zeitung) and were compiled and published in 1915 as Fünf Monate an der Ostfront: Kriegsberichte (Five months on the Eastern Front: War reports). Brandt's reports were more than just army-approved press releases. He wrote in a way that constructed a bridge between the home front and the front lines. In the process he employed techniques now associated with literary journalism. With a clear point of view, he told his story through a sequence of scenes, instead of a simple historical narrative, and included genuine dialogue and status details. While scholars of German literary journalism point to Egon Erwin Kisch as the originator of German literary journalism, this study suggests Brandt should be considered an early practitioner of literary journalism in the German language. More interestingly, Brandt's particular brand of literary journalism had an unmistakably conservative nationalist perspective, thus suggesting that it is possible to have a conservative form of literary journalism. © 2019 Literary Journalism Studies. All Rights Reserved.
Keywords: Conservative literary journalism; Germany; Propaganda; Rolf Brandt; Russia; World War I; dept.his; peer-reviewed; ⛔ No DOI found

Focus introduction: Swarms, herds, and peoples—examinations of interspecies dynamics in China - Bello, David A.; Thompson, C. Michele (East Asian Science, Technology, and Medicine, 2018)
As its title suggests, this Focus draws our attention to the shift in perspective brought about by environmental history, compared to the more traditional approaches of history of science. Here human knowledge of and interaction with animals are understood as part of a historically variable system that encompasses both the human realm and its environment, a system in which the various components interact and shape each other dynamically.
Keywords: dept.his; peer-reviewed; ⛔ No DOI found

Welcoming ruin: The Civil Rights Act of 1875 - Friedlander, Alan; Gerber, Richard Allan (Brill, 2018)
Keywords: dept.his

Edification through the memory of sins - Chrissidis, Nikolaos A. (Canadian-american Slavic Studies, 2018)
The article explores the practical uses of Eastern Orthodox indulgences as certificates of absolution with a dual function (as mnemonic tools and as public certificates of good standing with the church) in the early modern period. © KONINKLIJKE BRILL NV, LEIDEN, 2018
Keywords: Eastern Orthodox indulgences; Eastern Orthodox penitential practices; Mese katastasis ton psychon; Patriarch Dositheos of Jerusalem; Purgatory; Synchorochartia; dept.his; peer-reviewed

“Notorious abuse,” “traditious ignorance,” and “ambitious incroachment” in seventeenth-century Dutch, English, and French maps of North America - Petto, Christine M. (Cartographica: The International Journal for Geographic Information and Geovisualization, 2018)
In consideration of Richard Daniel’s alarmed discourse found in the text accompanying his map of the English empire in America (1679), one must investigate the supposedly offending French, English, and Dutch maps of the second half of the seventeenth century for North America and, in particular, the region of the Atlantic coastline and the rhetorical devices of possession found on or in these geographical works. In addition to looking at territorial boundaries, one should also make note of armorial bearings, ships with naval ensigns, toponyms and their placement on the territory, dedicatory cartouches, legends with geographical or historical information, native scenes, and symbols for settlement. In addition to attention to possible constraints on or from the map trade, one must consider the correspondence between colonial officials and their respective governments regarding boundaries, encroachment, sovereignty, or the need for maps with a particular focus on the North American coastline. This correspondence reflects the state’s point of view, which in turn was often manifested on maps and in geographical works. Interestingly intertwined with this outspoken sense of rightful possession were the contemporary claims from some quarters that the cartographic enterprise of the late seventeenth century now embraced an empirical approach, as well as the seemingly opposing thread of the economic realities of the print trade, which often used old copper plates with little to no cartographic revision, so that long after political, economic, or military actions resulted in an “adjustment” in possession, printed maps, atlases, and other geographical works still reflected earlier circumstances. © University of Toronto Press
Keywords: Cartography; Colonies; England; France; History; Netherlands; New England; New Netherland; North America; Seventeenth-century maps; The Netherlands; United Kingdom; colonialism; dept.his; economic history; empirical analysis; historical cartography; human settlement; peer-reviewed; seventeenth century; territorial dispute

War and Environment - Smith, Jason W. (The Routledge History of Global War and Society, 2018)
Scholars have offered at least four distinct but interrelated conceptual frameworks for examining the relationship between militaries and the natural world.
Keywords: dept.his

Hope in an ad: Teaching consumerism and idealized womanhood using 1920s advertisements - Carter-David, Siobhan (Advertising & Society Quarterly, 2018)
Keywords: dept.his; peer-reviewed

Computer systems: Digital design, fundamentals of computer architecture and assembly language - Elahi, Ata (Springer International Publishing, 2018)
This textbook covers digital design, fundamentals of computer architecture, and assembly language. The book starts by introducing basic number systems, character coding, basic knowledge in digital design, and components of a computer. The book goes on to discuss information representation in computing; Boolean algebra and logic gates; sequential logic; input/output; and CPU performance. The author also covers ARM architecture, ARM instructions and ARM assembly language which is used in a variety of devices such as cell phones, digital TV, automobiles, routers, and switches. The book contains a set of laboratory experiments related to digital design using Logisim software; in addition, each chapter features objectives, summaries, key terms, review questions and problems. The book is targeted to students majoring Computer Science, Information System and IT and follows the ACM/IEEE 2013 guidelines. • Comprehensive textbook covering digital design, computer architecture, and ARM architecture and assembly • Covers basic number system and coding, basic knowledge in digital design, and components of a computer • Features laboratory exercises in addition to objectives, summaries, key terms, review questions, and problems in each chapter
Keywords: ARM architecture; ARM processors; Assembly language; Boolean algebra; Computation theory; Computer architecture; Digital designs; Digital devices; Digital television; Information representation; Laboratory exercise; Laboratory experiments; Number system; Numbering systems; Reviews; Sequential logic; Textbooks; dept.csc

Confucius and filial piety - Radice, Thomas (A Concise Companion to Confucius, 2017)
Keywords: dept.his

Dreams of antiquity: H. P. Lovecraft’s great Roman dream of 1927 - Nakamura, Byron (Lovecraftian Proceedings No. 2, 2017)
This second volume of Lovecraftian Proceedings contains a wealth of cutting-edge scholarship on the dreamer from Providence, including substantial articles from both recipients of the S. T. Joshi Endowed Research Fellowship for H. P. Lovecraft at Brown University.  Lovecraftian Proceedings fosters exploration of Lovecraft as a rationalist who created an elaborate cosmic mythology, and how this mythology was influenced by, and has come to influence, numerous other authors and artists. The papers which comprise Lovecraftian Proceedings were presented during a key part of the NecronomiCon Providence convention, the Dr. Henry Armitage Memorial Symposium. TABLE OF CONTENTS Introduction             Dennis P. Quinn Dreams of Antiquity:  H. P. Lovecraft's Great Roman Dream of 1927Byron Nakamura The Poet’s Nightmare: The Nature of Things According to LovecraftSean Moreland Reordering the Universe: H. P. Lovecraft’s Subversion of the Biblical DivineRené J. Weise Resisting Cthulhu:  Milton and Lovecraft’s Errand in the Wilderness Marcello Ricciardi “The Discriminating Urban Landscapist": Tradition and Innovation in the Architectural Writings of H. P. LovecraftConnor Pitetti Tentacles in the Madhouse: The Role of the Asylum in the Fiction of H. P. LovecraftTroy Rondinone Unspeakable Languages: Lovecraft Editions in Spanish Juan L. Pérez-de-Luque Color out of Mind: Correlating the Cthulhu Mythos Universe to the Autism Disorder SpectrumLars G. Backstrom Darwin and the Deep Ones: Anthropological Anxiety in "The Shadow over Innsmouth" and Other StoriesJeffrey Shanks The “Inside” of H. P. Lovecraft’s Supernatural Horror in the Visual Arts Nathaniel R. Wallace H. P. Lovecraft’s OptimismMatthew Beach Insider, Outsider: From the Commonplace to the Uncanny in H. P. Lovecraft’s Narration and DescriptionsDaphnée Tasia Bourdages-Athanassiou H. P. Lovecraft, Georges Bataille, and the Fascination of the Formless: One Crawling Chaos Seen Emerging from Opposite ShoresChristian Roy  Ripples from Carcosa: H. P. Lovecraft, True Detective, and the Artist-InvestigatorHeather Poirier Lovecraft for the Little Ones: ParaNorman, Plushies, and MoreFaye Ringel and Jenna Randall Contributors AppendixAbstracts of Papers Presented at the Dr. Henry Armitage Memorial Scholarship Symposium,NecronomiCon Providence 20-23 August, 2015Chair: Dennis P. Quinn Index
Keywords: dept.his

Li (ritual) in early Confucianism - Radice, Thomas (Philosophy Compass, 2017)
Keywords: dept.his

The implications of gia truyền: Family transmission texts, medical authors, and social class within the healing community in Vietnam - Thompson, C. Michele (South East Asia Research, 2017)
In Vietnamese medicine, gia truyen ("family recipes") refers to a set of texts, primarily in chu nôm (demotic Vietnamese characters), that preserves local knowledge about how practitioners in a specific family-based medical circle could use various plants and other materia medica to cure disease. This article traces the history of the transmission of gia truyen in the 19th and 20th centuries. It suggests that prior to the 1920s, gia truyen were written anonymously to protect the author's identity in the face of the Nguyen dynasty's repression of ch? nom writing. In the 1920s, precisely at the time that hán-nôm writing was being eclipsed by education in French and quoc ngu (Romanized Vietnamese), Vietnamese medical practitioners experienced a renaissance in the writing of chu nôm gia truyen. Moreover, chu nôm writing in the gia truyen genre continued until at least the 1990s. ©SOAS University of London 2017.
Keywords: Chu nom; Colonial; Materia medica; Medical texts; Traditional medicine; Viet Nam; class; dept.his; disease treatment; historical perspective; medical geography; nineteenth century; social history; traditional knowledge; traditional medicine; twentieth century

Method mourning: Xunzi on ritual performance - Radice, Thomas (Philosophy East and West, 2017)
Keywords: dept.his

The journey from discovery to scientific change: scientific communities, shared models, and specialised vocabulary - Roe, Sarah M (International Studies in the Philosophy of Science, 2017)
Scientific communities as social groupings and the role that such communities play in scientific change and the production of scientific knowledge is currently under debate. I examine theory change as a complex social interaction among individual scientists and the scientific community, and argue that individuals will be motivated to adopt a more radical or innovative attitude when confronted with striking similarities between model systems and a more robust understanding of specialised vocabulary. Two case studies from the biological sciences, Barbara McClintock and Stanley Prusiner, help motivate the idea that sharing of models and specialised vocabulary fill the gap between discovery and scientific change by promoting the dispersal of important information throughout the scientific community. © 2017 Open Society Foundation.
Keywords: dept.his

Extended mechanistic explanations: expanding the current mechanistic conception to include more complex biological systems - Roe, Sarah M; Baumgaertner, Bert (Journal for General Philosophy of Science, 2017)
Mechanistic accounts of explanation have recently found popularity within philosophy of science. Presently, we introduce the idea of an extended mechanistic explanation, which makes explicit room for the role of environment in explanation. After delineating Craver and Bechtel’s (2007) account, we argue this suggestion is not sufficiently robust when we take seriously the mechanistic environment and modeling practices involved in studying contemporary complex biological systems. Our goal is to extend the already profitable mechanistic picture by pointing out the importance of the mechanistic environment. It is our belief that extended mechanistic explanations, or mechanisms that take into consideration the temporal sequencing of the interplay between the mechanism and the environment, allow for mechanistic explanations regarding a broader group of scientific phenomena. © 2016, Springer Science+Business Media Dordrecht.
Keywords: Complex systems; Explanation; Mechanism; Mechanistic environment; dept.his